Repairable electronic products for the circular economy: a review of design for repair features, practices and measures to contrast obsolescence - Nataliia Roskladka; Gianmarco Bressanelli; Nicola Saccani; Giovanni Miragliotta (Discover Sustainability)
Abstract The current linear economy, with its “take-make-dispose” approach, has led to an unprecedented level of waste generation related to the end-of-life of electronics products, entailing huge impacts on climate change, pollution and resource depletion. Against this trend, product repairability is a preferred Circular Economy strategy to extend product lifespan and contrast obsolescence. It is strongly advocated by consumer movements (“Right to Repair”) and supported by environmental policies, such as the European Union Circular Economy Action Plan. To be effective, a repairability strategy has to be defined at the product design stage. However, many electronics products are still designed with built-in obsolescence. In literature, Design for Repair (DfR) strategies are presented in a fragmented way, with their role in fighting obsolescence and enabling a Circular Economy being under-investigated. Through a systematic literature review, this article aims to identify the product design elements (DfR features) and detailed practical actions (DfR practices) that facilitate the repairability of products, preventing different types of product obsolescence as well as finding the indicators (DfR measures) to quantify DfR features to assess the level of product repairability. The systematic analysis revealed that, while DfR features (and the relative practices and measures) that contrast mechanical, technological and service obsolescence have been frequently investigated by the literature, lower attention has been dedicated to DfR features preventing relative obsolescence. These practices deserve more theoretical and practice-oriented research. The identified DfR features, practices and measures are then organized into a comprehensive framework, which sheds light on the operationalization of repair as a CE strategy and support designers and R&D engineers in designing products to be repaired. The framework provides guidelines to product designers and engineers to operationalize the ‘Plan-Do-Check-Act’ cycle of product development for repairability to increase product circularity. The framework also supports policymakers in the benchmarking and fine-tuning of currently policy adopted methods for assessing repairability at the product level.